IDENTIFIKASI MATERI LOKAL SEBAGAI SUMBER BELAJAR SAINS BIOLOGI SMP DI KABUPATEN MUARA ENIM - Ekapty Tyas Pradietha; Meilinda Meilinda; Khoiron Nazip (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Sriwi, 2014)
Abstract: The purposes of this study was to find out the information about local material covered local wisdoms, local potentials, and environmental local problems of Muara Enim regency as a requirements to fill the learning sources of Biology course in junior high schools. This study has been conducted in Muara Enim regency and involved five subdistricts that have been choosen based on its topography condition. Ujan Mas and Lawang kidul represented the lowland. Tanjung Agung, Semende darat Tengah and Semende Darat Ulu represented the highland. Descriptive method was applied in this study and the information about local material was found out through observation, interview and related literature. The result of this study showed that there were 15 local materials that has been identified and can be used as the learning sources covered local wisdom, there were people that were accustomed to live in rumah panggung; saving the agriculture outcome in tengkiang; and people habit to keep tebat mandian as a place that used for saving clean water. Meanwhile, for the local potentials, there were freshwater fish cultivation, tree nurseries in PT Bukit Asam (Persero) Tbk; variety plants around Curup Tenang Bedegung waterfall ; fish cultivation in fish seed center; rice field; and waste processing in PT Bukit asam (Persero) Tbk. In addition, for the environmental local problems were air pollutions that caused by rubber production in a rubber factory; burning and producing process of brick; bathing process and domestic waste in the river; vast growing of water hyacinth; the effect of sand and river stone mining; and the effect of coals mining that damage the ecosystem. The significant of this study hopefully can be used as the reference for the teachers doing biology teaching and learning process in junior high school and also can be used for developing the learning material of local material in Muara Enim regency. Key words : local material, learning sources, science learning, Muara Enim